2015
DOI: 10.1016/j.devcel.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Stromules Function during Innate Immunity

Abstract: Summary Inter-organellar communication is vital for successful innate immune responses that confer defense against pathogens. However, little is known about how chloroplasts, which are a major production site of pro-defense molecules, communicate and coordinate with other organelles during defense. Here we show that chloroplasts send out dynamic tubular extensions called stromules during innate immunity or exogenous application of the pro-defense signals, hydrogen peroxide (H2O2) and salicylic acid (SA). Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
443
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(477 citation statements)
references
References 36 publications
27
443
4
3
Order By: Relevance
“…Although the biological significance of stromules remains unclear, accumulating evidence indicated that the stromules function in trafficking proteins (Krenz et al, 2012;Hanson and Sattarzadeh, 2013;Caplan et al, 2015). Stromules have been found to be induced by effector-triggered immunity, and chloroplastlocalized N receptor-interacting protein1 (NRIP1) was transported from chloroplasts into the nucleus during this process through stromules (Caplan et al, 2015). Moreover, in Abutilon mosaic virus-infected leaves, a plastid-targeted heat shock cognate 70-kD protein (chaperone) was found to interact with Abutilon mosaic virus movement protein in the stromules (Krenz et al, 2010), which may facilitate viral transport from chloroplasts into a neighboring cell or the nucleus (Krenz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the biological significance of stromules remains unclear, accumulating evidence indicated that the stromules function in trafficking proteins (Krenz et al, 2012;Hanson and Sattarzadeh, 2013;Caplan et al, 2015). Stromules have been found to be induced by effector-triggered immunity, and chloroplastlocalized N receptor-interacting protein1 (NRIP1) was transported from chloroplasts into the nucleus during this process through stromules (Caplan et al, 2015). Moreover, in Abutilon mosaic virus-infected leaves, a plastid-targeted heat shock cognate 70-kD protein (chaperone) was found to interact with Abutilon mosaic virus movement protein in the stromules (Krenz et al, 2010), which may facilitate viral transport from chloroplasts into a neighboring cell or the nucleus (Krenz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast stromules, which are thin projections of stroma-filled tubules emerging from the surface of chloroplasts, have been reported to be associated with abiotic and biotic stresses (Gray et al, 2012;Krenz et al, 2012;Caplan et al, 2015). Although the biological significance of stromules remains unclear, accumulating evidence indicated that the stromules function in trafficking proteins (Krenz et al, 2012;Hanson and Sattarzadeh, 2013;Caplan et al, 2015). Stromules have been found to be induced by effector-triggered immunity, and chloroplastlocalized N receptor-interacting protein1 (NRIP1) was transported from chloroplasts into the nucleus during this process through stromules (Caplan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplast stromules also might function in innate immunity. During this response, numerous stromules surround the nuclei, and the intensity of their connection correlates with the accumulation of chloroplast-derived defense protein and (interestingly) H 2 O 2 in the nucleus (Caplan et al, 2015). The association of the ER with the chloroplast is an example of the physical interaction of the chloroplast with another organelle.…”
Section: Reverse Coupling Of Redox Signaling To the Chloroplastmentioning
confidence: 99%
“…Recently, it was reported that the application of H 2 O 2 or SA to tobacco (Nicotiana tabacum) leaves stimulates the rapid generation of stromules (within 1 h; Caplan et al, 2015). Moreover, the formation of stromules is regulated by a specific protein localized on the chloroplast outer envelope membrane, named CHLOROPLAST UNUSUAL POSITIONING1 (CHUP1).…”
Section: Organellar Extensions: a Hotline To The Nucleus?mentioning
confidence: 99%